Mechanical Needling with Sterile Water versus Steroids Injection for Facet Joint Syndrome: A Retrospective Observational Study - Areerat Suputtitada; Carl P. C. Chen; Krit Pongpirul (Pain Research and Management)
Objective. This present study aimed to explore the clinical effects of ultrasound-guided (USG) mechanical needling with sterile water injection for lumbar facet joint syndrome. Methods. This was a retrospective cohort study that assessed the clinical outcome of ageing patients who received USG mechanical needling with sterile water injection. In addition, the clinical outcome of age- and gender-matched patients randomly selected from patients who received mechanical needling with sterile water was compared to the patients injected with steroids in a 2 : 1 ratio. The data were extracted from the medical records of ageing patients with facet joint syndrome who received USG injection at the lumbosacral spine by the first author. Low back pain or axial pain, and leg pain or radicular pain were assessed by the visual analogue scale (VAS), and gait ability with walking distance was obtained at 6 different time points. Results. A total of 4,276 medical records were examined. Four thousand two hundred twenty-eight ageing patients received needling with sterile water injection and found that the efficacy lasted up to 6 months. Ninety-six patients were compared with 48 patients who received steroid injection. Those who received steroids had less back and leg pain at 1 week after injection; however, pain returned at 3 months and 6 months after injection. Conclusions. USG mechanical needling with sterile water could help relieve axial and radicular pain for at least 6 months. Reduced sensitization and removal of calcification and fibrosis were all possible mechanisms.Keywords: Mechanical needling, Sterile water, Ultrasound guided (USG) injection, Facet joint syndrome, Pain